Exploring fixed points via admissibility criteria for fuzzy theta f-weak contractions - Moussaoui, Abdelhamid (Nonlinear Analysis: Modelling and Control, 2025)
In this study, we introduce a new class of fuzzy contractions, called fuzzy α-η-θf -weak contractions, and establish fixed point results within the framework of complete fuzzy metric spaces. A fuzzy metric space generalizes the concept of a metric space by defining the “distance” between two points ω and υ using a function ϑ(ω, υ, ς) that quantifies the degree of nearness between these points for a parameter ς > 0. This parameter ς reflects various factors influencing the closeness of the points, making fuzzy metric spaces a powerful tool for modeling uncertainty and imprecision in mathematical contexts. Based on this framework, we prove several fixed point theorems addressing the existence and uniqueness of fixed points for such contractions. By carefully selecting specific forms of the functions θf, α, and η, our primary results can be adapted to yield a variety of significant corollaries. Furthermore, our findings leverage admissible and auxiliary functions to provide a broader framework that consolidates, extends, and refines existing results in fixed point theory.